Towards private sector collaboration in aid practice: internal challenges faced by development NGOs. Issue 5 (3rd July 2020) - Hakkarainen, Minna
ABSTRACT: It is widely acknowledged that achieving the Sustainable Development Goals requires the contribution of all sectors of society, including profit-driven businesses. As the private sector gains greater visibility in development discourses, development NGOs are increasingly seeking new, more profound forms of collaboration with businesses. Yet, although the notion of a multi-stakeholder partnership has consistently appeared in recent formulations of aid policy, there is little understanding of factors affecting the ability of NGOs to capitalise on private sector collaboration. Deriving from in-depth interviews of Finnish development NGOs, this article offers insights into the internal challenges NGOs face when establishing collaboration with businesses.